Las calcitas de muzo (colombia) variedad "granizo" (1985)
Within the rich mineralogical association found in the Muzo area, there is a variety of calcite, long time known by the miners in the region, and named by them "Granizos" ("Hails"). I ts genesis is different from other calcite varieties found at the same area, requiring special temperature and pressure conditions. Morphological studies have shown a "rounding" of the samples, with a tendency to a "cube-like" aspect, due to many form varieties and to presence of twinning.  The term "Granizo" should de kept in use as a Colombian variety of calcite; the characteristic twinning should be termed "Muzo twinning".